Green synthesis of novel spiropyrazoline-indolinones in neutral deep eutectic solvents and DFT studies - Zubi Sadiq; Ambreen Ghani; Muhammad A. Hashmi; A. Dahshan; Shahnaz; Samiah H. Al-Mijalli; Munawar Iqbal; Erum A. Hussain (Heliyon, 2024)
Novel spiropyrazoline-indolinones (4a–t) have been synthesized successfully in neutral deep eutectic solvents by reacting 5-Cl/Br-isatin (1a–b) with aromatic ketones (2a–b) and a variety of substituted hydrazines (3a–e) in good to excellent yields. This eco-friendly straightforward synthetic protocol discloses good functional group compatibility. The conventional synthetic approach was compared with the greener route of microwave-assisted synthesis of spiropyrazolines using ethanol. This approach utilized mild reaction conditions which furnished high yields in short reaction time employing one pot two-step multicomponent. All new compounds were structurally confirmed by detailed spectroscopic analysis and density functional theory calculations. This method provides efficient access to spiropyrazole derivatives using biodegradable and green solvent.